Estudo comparativo da concentração de glicose salivar e sanguínea em pacientes diabéticos tipo 2 - Vasconcelos, Ana Carolina Uchoa (2007)
Diabetes mellitus is an endocrine disease, which causes alteration in assimilation, metabolism and balance of the blood glucose concentration. It is believed that the high level of blood glucose is linked to the development of buccal alterations; however, there is some controversy in the studies that aim to compare the concentration of blood and salivary glucose in diabetic patients. The objective of this paper is to comparatively evaluate the concentration of blood and salivary glucose as well as the salivary flow and xerostomia in type 2 diabetic and non-diabetic patients. Eighty adult subjects of both sexes have been selected, being 40 adults diabetic of the experimental type and 40 adults non-diabetic belonging to control. The total in-rest and stimulated salivary flow has been determined as well as the concentration of peripheral blood and salivary glucose. Descriptive analysis was carried out and Mann-Whitney and qui-square tests were applied considering significant values of p<0,05. The average value of salivary glucose in diabetic patients was 14,03±16,76 mg/dl and in the control group, 6,35±6,02 mg/dl, with p= 0,036. The capillary blood glucose in diabetic patients presented an average value equivalent to 213,23±87,98 mg/dl and, in non-diabetic patients it was equivalent to 99,15±13,72 mg/dl, with p= 000. The average value for the in-rest salivary flow was 0,21±0,16 ml/min in diabetic patients and 0,33±0,20 ml/min in the control group with p= 0,002. The stimulated salivary flow was lower in the group of diabetic patients, with an average of 0,63±0,43 ml/min, in relation to the control group, which presented an 1,20±0,70 ml/min average, with p= 0,00. Out of the diabetic patients, 45% had hyposalivation contrasting to 2,5% out of the non-diabetic patients, with p=0,00. Xerostomia was reported in 12,5% of diabetic patients and 5% of non-diabetic patients, with p=0,23. We can conclude that the salivary glucose concentration was significantly higher in the experimental group and that there was no correlation between the salivary and blood glucose concentration in diabetic patients. The total salivary flows were significantly reduced in diabetic patients and there was no significant difference as to the presence of xerostomia in both groups.